Pengaruh Komitmen Organisasi dan Kompetensi Pegawai terhadap Kualitas Pelayanan Administrasi Terpadu Kecamatan di Kantor Kecamatan Jasinga Kabupaten Bogor - Pepeng Supendi; A.H. Rahadian (Jurnal Ilmu Administrasi Publik, 2021)
Commitment and Civil Servant Competence toward the Service Quality of Districts Integrated Administrative in Jasinga District Office, Bogor Regency, partially and simultaneously. This study uses explanatory research methods with a quantitative descriptive approach. The population in this study were recipients of PATENT services in Jasinga District, Bogor Regency, the period January - December 2018 was 1,335 people, with Slovin (5%) obtained 308 samples. The results showed: There is a positive and significant Influence of Organizational Commitment toward the Service Quality of Districts Integrated Administrative in Jasinga District Office, Bogor Regency, with a magnitude of influence of 52.9%. There is a positive and significant Influence of Civil Servant Competence toward the Service Quality of Districts Integrated Administrative in Jasinga District Office, Bogor Regency, with a magnitude of influence of 64%. There is a positive and significant Influence of Organizational Commitment and Civil Servant Competence simultaneously toward the Service Quality of Districts Integrated Administrative in Jasinga District Office, Bogor Regency, with an influence of 65.2%.